2017
DOI: 10.2139/ssrn.3091142
|View full text |Cite
|
Sign up to set email alerts
|

On Monetary and Non-Monetary Interventions to Combat Corruption

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…This suggests that in monetary payoffs trials, participants with greater negative reciprocity experience unexpected cooperation from opponents more unexpectedly and thus exhibit a larger dFRN following participants’ aggression. This finding supports several prior evidence demonstrating that the stronger preference for an eye for an eye or tit‐for‐tat (i.e., negative reciprocity) strategy always arises in the marketable orientated behavior (Banerjee & Mitra, 2018; Cox & Deck, 2005; Greco et al., 2019). Accordingly, when behavior is associated with monetary payoffs, participants have a stronger expectation that aggressive behavior should be returned in‐kind.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that in monetary payoffs trials, participants with greater negative reciprocity experience unexpected cooperation from opponents more unexpectedly and thus exhibit a larger dFRN following participants’ aggression. This finding supports several prior evidence demonstrating that the stronger preference for an eye for an eye or tit‐for‐tat (i.e., negative reciprocity) strategy always arises in the marketable orientated behavior (Banerjee & Mitra, 2018; Cox & Deck, 2005; Greco et al., 2019). Accordingly, when behavior is associated with monetary payoffs, participants have a stronger expectation that aggressive behavior should be returned in‐kind.…”
Section: Discussionsupporting
confidence: 89%
“…Although Nagin (2013) argues that the probability of punishment 3 and not the severity of punishment serves as a deterrent, the prospect theory (Tversky & Kahneman, 1992) predicts that the relative effects of increasing the probability or size of punishment would depend on the starting point given that both the functions of subjective probability and subjective value of a loss are non-linear. The latter prediction is supported, for example, by Banerjee and Mitra (2018) who experimentally demonstrated that despite the same expected value of punishment, high fines with a low probability decreased the corrupt behavior, unlike lower fines with higher probability that did not have any observable effect. In a similar vein, it was shown that even a small probability of severe punishment in the form of a sudden death (i.e., after being discovered, the players would lose all of their earnings from the experiment above the show-up fee) led to a significant reduction in offering and accepting bribes (Abbink, Irlenbusch, & Renner, 2002).…”
Section: Literature Reviewmentioning
confidence: 83%
“…Because of the many negative effects of corruption on society, 1 there is a lot of interest in the study of factors influencing corrupt behavior and examining effects of various anticorruption policies, oftentimes in laboratory settings. Although some of the explored approaches are less typical, such as staff-rotation (Ryvkin & Serra, 2012), competition among public officials (Shleifer & Vishny, 1993), anonymous public reporting (Ryvkin, Serra, & Tremewan, 2017) or ethics education (Banerjee & Mitra, 2018), most attempts at curbing corruption focus on the probability and size of a punishment (Abbink & Serra, 2012). Despite the amount of research interest in the effects of these two factors, the results remain mixed and inconclusive (Boly & Gillanders, 2018), possibly because many studies employ one-shot tasks and explore only a limited number of combinations of punishment probabilities and sizes.…”
Section: Introductionmentioning
confidence: 99%
“…: Blais & Young, 1999; Frank et al, 1993; Ifcher & Zarghamee, 2016; Wang et al, 2011). For instance, practical experience with experiments can have significant and durable effects on preferences (Xiao & Houser, 2014), but effects of abstract ethical instruction can be comparatively limited and short termed (Banerjee & Mitra, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Abstract and theoretical education alone can be less effective. According to Banerjee and Mitra (2018), ethical instruction kept only a limited number of people from claiming or accepting bribes and the effect was not very durable. These considerations are preliminary and not complete, but they reveal that answering the question whether people trained in Economics are different should begin with summarizing what we know about the different factors involved in human moral decision making and preference formation.…”
Section: Interpersonal Processes In Moral Decision Makingmentioning
confidence: 99%